The metaverse handbook : innovating for the internet's next tectonic shift - Terry, Quharrison; Skee, DJ, 1983- (John Wiley & Sons, 2022)
"In The Metaverse Handbook: Innovating for the Internet's Next Tectonic Shift, a duo of experienced tech and culture experts delivers a can't-miss guide to participating in the most promising new technology since the advent of the web. Through dozens of metaverse creator case studies and concise, actionable insights, you'll walk away from this book understanding how to explore and implement the latest metaverse tech emerging from blockchain, XR, and web3. In The Metaverse Handbook, you'll discover: What the metaverse is, why you should care about it, and how to build your metaverse strategy The history of the metaverse and primers on critical technologies driving the metaverse, including non-fungible tokens, XR, the blockchain, and web3 How to unearth unique metaverse opportunities in digital communities, commerce, and immersive experiences As the metaverse has rapidly become the technology platform and marketing buzzword of the future, this new reality for companies, creators, and consumers is not easily understood at the surface level. Those who aim to be at the forefront of this exciting new arena must first understand the foundations and central technologies of the metaverse. An essential resource for digital professionals, creators, and business leaders in the vanguard of the coming technology revolution, The Metaverse Handbook provides the go-to roadmap for your journey into the metaverse." --Amazon.com.